BEGONIA MARIACHRISTINAE (BEGONIACEAE), A NEW SPECIES FROM NORTHERN MYANMAR - Wahlsteen, E. (Edinburgh Journal of Botany, 2018)
Begonia mariachristinae Wahlsteen, a new endemic species from Kachin, northern Myanmar, is described and illustrated. The new species is characterised by its combination of four perianth segments in the female flower, two ovary wings, two locules, two styles and a dioecious breeding system.